2018
DOI: 10.1186/s12964-018-0261-y
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell polyomavirus and Langerhans cell neoplasm

Abstract: BackgroundThe relationship between various external agents such as pollen, food, and infectious agents and human sensitivity exists and is variable depending upon individual’s health conditions. For example, we believe that the pathogenetic potential of the Merkel cell polyomavirus (MCPyV), the resident virus in skin, is variable and depends from the degree of individual’s reactivity. MCPyV as well as Epstein-Barr virus, which are normally connected with humans under the form of subclinical infection, are thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…The inflammatory nature of LCH lesions raises the possibility that infection and immune dysregulation may be the mechanisms of pathogenesis ( 52 ). Several viruses have been studied as potential etiological factors of LCH, including EBV ( 53 ), human herpesvirus 6 (HHV-6) ( 54 ), cytomegalovirus (CMV) ( 55 ), herpes simplex virus (HSV) ( 56 ), and Merkel-cell polyoma virus (MCV or MCPyV) ( 57 ). Murakami reported that MCV-related molecules are present in more than half of LCH cases, and in some dermatopathy lymphadenopathy cases ( 58 ), and that three LCS cases were positive for viral DNA sequences ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory nature of LCH lesions raises the possibility that infection and immune dysregulation may be the mechanisms of pathogenesis ( 52 ). Several viruses have been studied as potential etiological factors of LCH, including EBV ( 53 ), human herpesvirus 6 (HHV-6) ( 54 ), cytomegalovirus (CMV) ( 55 ), herpes simplex virus (HSV) ( 56 ), and Merkel-cell polyoma virus (MCV or MCPyV) ( 57 ). Murakami reported that MCV-related molecules are present in more than half of LCH cases, and in some dermatopathy lymphadenopathy cases ( 58 ), and that three LCS cases were positive for viral DNA sequences ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the former model, LCH is classified as an inflammatory myeloid neoplasm predominantly caused by mutations in the MEK/ERK pathway, frequently affecting BRAF and MAP2K1 (50,(53)(54)(55)(56). A role of viral infections in LCH pathogenesis has been previously considered, but without having definitive conclusions (57,58). LCH patients have not been reported to display innate immunodeficiency or defined susceptibility to infectious agents (59).…”
Section: Discussionmentioning
confidence: 99%
“…Despite MCCN tumor having a high mutational burden, MCCP harbours a 100-fold lower mutational load (17). According to the Surveillance, Epidemiology, and End Results (SEER) Program, the MCC 5-year survival rate is 76, 53 and 19% for localized, regional and distant disease, respectively, with an overall combined rate of 63% (18)(19)(20)(21). MCC global incidence ranges 0.1-1.6 cases/100,000 individuals (22).…”
Section: Introductionmentioning
confidence: 99%